Bioenergetics and stellar luminosities. Issue 3 (12th October 2017) - Sivaram, C; Arun, K; Kiren, O V
Abstract: We draw attention to a curious coincidence wherein the most (steadily emitting) luminous objects in the Universe from stellar X-ray sources to ultra-luminous quasars and Ultra Luminous Infrared Galaxies, steadily emit a power per unit mass, which is just the same value as the maximal metabolic rate in (warm-blooded) bio-organisms.